1968
DOI: 10.4319/lo.1968.13.2.0250
|View full text |Cite
|
Sign up to set email alerts
|

A PERSISTENT DIURNAL RHYTHM IN CHAOBORUS LARVAE. I. THE NATURE OF THE RHYTHMICITY1

Abstract: Larvae of Chaoborus punctipennis Say (Diptera: Culicidae) were maintained under constant conditions in two 152‐ × 10‐cm columns containing lake water and sediments. Visual counts of the larvae in the columns were made hourly with a flashlight equipped with a red filter and darkened reflector. Activity was observed during dark periods; however, no activity was observed during light periods. A diurnal rhythm of activity persisted up to 10 days in constant darkness. The phase of the rhythm was reset by entrainmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

1982
1982
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 2 publications
1
16
1
Order By: Relevance
“…LaRow (1968) suggested that within the sediments the larvae undergo a circadian pattern of movements that brings the animals to the mud surface near dusk, where they enter the water in response to a threshold light intensity (Swift and Forward 1988) or other factors as suggested in this study.…”
Section: Iscussionmentioning
confidence: 53%
“…LaRow (1968) suggested that within the sediments the larvae undergo a circadian pattern of movements that brings the animals to the mud surface near dusk, where they enter the water in response to a threshold light intensity (Swift and Forward 1988) or other factors as suggested in this study.…”
Section: Iscussionmentioning
confidence: 53%
“…While C. flavicans and C. trivittatus larvae co-occurred with fish, C. americanus larvae were strongly associated with fishless lakes. The first instar larvae can benefit from a size refuge and escape prédation, but larger final instars adopt predator avoidance behaviours such as diel vertical migration (LaRow 1968(LaRow , 1969. However, this behaviour is not observed in C americanus larvae, and so it only occurs in fishless lakes von Ende 1979;Wissel et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As in the limnetic area, in this study it was observed that Daphnia pulex was more abundant in presence of fish rather than in absence and this could be correlated with the high density of Chaoborus larvae present into the water column during daytime. Fish are known to influence Chaoborus larvae composition and distribution , von Ende 1979, Wissel et al 2003 and some Chaoborus species make diurnal migration to avoid fish prédation (LaRow 1968(LaRow , 1969. Their absence from the nekton samples offishpresent lakes may result from direct prédation by brook trout or from behavioural change as a response to fish prédation.…”
Section: Nekton Community Structurementioning
confidence: 99%
“…Zooplankton cultures were exposed to continuous light of a constant intensity in order to dampen LaRow (1968LaRow ( , 1969, Hagerman (1969), Hart & Allanson (1976), and others have found endogenous rhythms of swimming activity in cladoceran, copepod and ostracod zooplankton, and Buchanan & Goldberg (1981) observed a strong relationship between the prestimulus swimming activity and the strength of the phototactic response for Daphnia after a stimulus is applied . The spectral distribution of the light source to which zooplankton are adapted can influence the photosensitivity of the animals .…”
Section: Methodsmentioning
confidence: 99%